Embodying Authenticity in Higher Education. (September 2016) - Douglass, Laura
Abstract : Orienting to the community of higher education involves a learning experience that is authentic and embodied for one new college administrator. Reflecting on her experience, she articulates how her relationship to her body helps to understand and respond to the tensions of engaging with a scholarly community.